Development of Scientific Activity in Humanistic Network for Science and Technology - Tanko Titus Auta; Sanglar Polnok; Ilyas Ibrahim; Heru Santoso Wahito Nugroho (Humanistic Network for Science and Technology (HNST), 2019)
The Humanistic Network for Science and Technology (HNST) has been established in order to help advance science and technology, through scientific activities. After reaching the age of 2 years, HNST has achieved significant developments in carrying out its ambition to actively participate in advancing science and technology and on an international scale. In future plans, HNST will focus on expanding journals, publishing books, extending training and assistance as well as collaboration with government agencies. Keywords: HNST, science and technology, scientific activities